Prevalence of anemia and associated factors in patients with heart failure admitted to Jimma university medical center - Elsah Tegene; Abdulkadir Mohammed; Tamirat Godebo; Gaddisa Desu; Edosa Tadasa (BMC Cardiovascular Disorders)
Abstract Background Anemia is common among adults with heart failure and is linked to increased risks of illness, decreased physical abilities, lower quality of life, more hospital visits, and higher mortality rates. In Ethiopia, about 23% of reproductive-age women and 18% of adult men suffer from anemia. However, data is lacking about its prevalence and associated factors in admitted heart failure patients in our setup. Objectives To determine the prevalence of anemia and associated factors in heart failure patients who were admitted to the emergency and medical ward at Jimma University Medical Center, Southwest Ethiopia. Methods A cross-sectional study was conducted among all heart failure patients admitted to Jimma University Medical Centre from September 1, 2023, to February 30, 2024. A complete blood count was done for these patients. The demographic data and clinical characteristics of study participants were collected using a structured questionnaire. Data was collected on patients’ admission and discharge and then data was cleared and entered into a computer using SPSS software version 26. Logistic regression was conducted to declare statistically significant variables with anemia at p-value < 0.05 with 95% CI of Adjusted odds ratio. Results A total of 269 participants were involved in the analysis with a mean age of 50.39 ± 18.08 years. The prevalence of anemia among patients with heart failure was 49.8% (43.7-55.9%). Anemia was statistically significant with hypokalaemia: AOR%CI; 3.88(1.6–9.43), creatinine level: AOR%CI; 3.58(1.74–7.38), re-admission: AOR%CI; 3.7(1.63–8.39), and length of hospital stay AOR%CI; 4.11(2.18–7.78). Conclusion In the current study, nearly half of admitted heart failure patients had anemia, which is associated with hypokalaemia, high creatinine level, readmission, and a longer duration of hospital stay. There was a high prevalence and clinical impact of anemia heart failure patients in our study.